Tuber qujingense and T. songlu, two new species from Yunnan, China - Wan, Shanping; Liu, Jianwei; Huang, Lanlan; Qin, Xiaomin; Liu, Wei; Yu, Fuqiang (Phytotaxa, 2021)
Tuber qujingense and T. songlu are described as new species based on both phylogenetic and morphological analyses. Phylogenetically, these two species are clearly distinct from described species of Tuber. Morphologically, these two species have whitish smooth ascomata, pubescent and prosenchymatous peridium and 1–4 spored asci; however, T. qujingense is characterized by its fusiform ascospores and taller alveolar walls (4.5–11 µm) while T. songlu has larger ellipsoid ascospores and lower alveolar walls (1–7 µm).